Pengaruh Kredit Usaha Rakyat Terhadap Pendapatan Usaha Mikro Dan Kecil Di Desa Selagik Kecamatan Terara Kabupaten Lombok Timur Provinsi Nusa Tenggara Barat (Studi Kasus Bank BRI Unit Terara) - Muhammad, Farhana; Rozali, Toyib (Universitas Hamzanwadi, 2017)
This research was aimed at knowing the effect of citizenry exertion credit toward income of Micro and Small Exertion in Selagik, Kecamatan Terara, abupaten Lombok Timur, Provinsi Nusa Tenggara Barat. The approach applied was quantitative untilizing deskcriptive research. The data were qualitative data and quantitative data with primary data and secondary as the data resource. Meanwhile, the data collection instrument applied were observation, interview, and documentation. The data analyses technique applied were bifilar regression analysis, classic assumption analysis, and compatibility testing consisted of 36 respondent of the Micro and Small Exertion (UMK) agent. The analysis instrument applied was SPSS 23.0 and Microsoft Exel 2007. Based on the result of the research, it showed that self modal and Citizenry Exertion Credit (KUR) modal was positively affect partially and simultaneously toward Mikro and Small Exertion (UMK) in Selagik; it can be seen from the variable coefficient score stated. Keywords : Micro and Small Exertion,Effect of Citizenry Exertion Credit